KRITIK SOSIAL DALAM LAGU ‘BAYAR! BAYAR! BAYAR!’ KARYA BAND SUKATANI: ANALISIS WACANA DENGAN PENDEKATAN PIERRE BOURDIEU - Putra, Sandi Justitia; Ningrum, Anisa Purwa; Wijaya, Arya Ananta (KAGANGA KOMUNIKA: Journal of Communication Science, 2025)
Sukatani's song "Pay! Pay! Pay!" is a musical expression that sharply criticizes the practice of extortion and corruption that are considered deeply rooted in the police institution. This study aims to analyze how the song's lyrics construct a discourse of resistance through the perspective of Pierre Bourdieu's theory, specifically the concepts of habitus, capital, and arena. Using a critical discourse analysis approach, this study reveals that the song's lyrics not only convey individual grievances but also represent the collective social experiences experienced by society when faced with unequal power structures. The community's habitus, oppressed by power relations, is reflected in the satirical expressions and protest tones that emerge in the song. Meanwhile, Sukatani's symbolic and cultural capital is utilized as a means to challenge the dominance of actors within the police arena. The research findings indicate that music, in this context, functions as an effective medium for social criticism and is able to foster critical awareness of structural injustice. Thus, this song becomes a form of cultural resistance that reveals economic inequality while mobilizing community solidarity for social change.   Keywords: Discourse, Corruption, Pierre Bourdieu, Social Critique